Determinants Of Banks’ Bottom Line: Evidence From Benchmarking Malaysian and Hong Kong Bank - Michael, Tinggi; Shaharudin, Jakpar; Ling, Ling (Universiti Malaysia Sarawak (UNIMAS), 2015)
The aftermath of 1997/1998 Asian-financial meltdown, witnessed a significant restructuring of banking sector, resulting in fewer but bigger conglomeration of banks in Malaysia. Banks are now challenged to raise profit to another level in order to be more resilient against any future financial onslaught. The need to learn from some of the world best banks should be explored. This empirical study therefore attempts to benchmark the determinants of banks’ bottom line in Malaysia vis-à-vis attributes affecting viability of the same industry in Hong Kong. The domain of the study involves gauging the impact of firm’s size, capital structure, liquidity, managerial efficiency, loans’ size on bottom line enjoyed by banking sector in Malaysia and Hong Kong. The panel data are extracted from the 11 major banks, operating from each country in Malaysia and Hong Kong for period 2002 to 2011. The fixed effect panel found that, bank size, capital structure and loans to customers have strong impact on bank bottom line in Malaysia. In contrast, managerial efficiency improves profit margin in Hong Kong banking sector.